Efforts to Deal with the Impact of Adolescent Pregnancy through a Holistic Approach: A Literature Review - Rahmawati, Iis; Murtaqib, Murtaqib (Nursing and Health Sciences Journal (NHSJ), 2024)
Teenage pregnancy, occurring at the age of 15-19 years, is a global public health problem with negative impacts for both mother and baby. The purpose of the study is to analyze the efforts that have been made in various countries in dealing with the impact of adolescent pregnancy to obtain strategies and recommendations that have the potential to create positive changes in handling the problem of adolescent pregnancy globally. This research method uses a literature review. The literature search process carried out in this literature review uses the database Scopus with a range of publication years 2019-2023. The search was conducted using several keywords "Teenage pregnancy" AND "impact". The findings of 10 journals show that teenage pregnancy has significant health and social impacts, including the risk of obstetric complications, high rates of maternal and infant mortality, and long-term consequences for mother and child. Factors such as low access to education, lack of knowledge about reproductive health, peer influence, and family problems trigger teenage pregnancy. The importance of a holistic approach involving collaboration between government, religious leaders, families, and educational institutions to prevent teenage pregnancy, increase knowledge of sexual education, and form positive, preventive attitudes needs to be done to reduce the risks and adverse effects associated with teenage pregnancy.